Impact of asymmetrical heating on the uncertainty propagation of flow parameters on wall heat transfers in solar receivers. (25th November 2021) - David, Martin; Toutant, Adrien; Bataille, Françoise
Abstract: Uncertainties may skew the understanding of experiments or numerical simulations results. The impact of the flow parameters uncertainties of measurement on wall heat flux is investigated in a non-isothermal turbulent channel flow. A heat transfer correlation dedicated to gas-pressurized solar receivers of concentrated solar tower power is used. Both symmetric and asymmetric heating conditions are tested. A sensitivity study is performed. The effects of the wall and bulk temperatures are analyzed in a large bulk-to-wall temperature ratio range. The Guide to the expression of Uncertainty in Measurement (GUM) is applied and provides an analytical expression of the uncertainty propagation. Assuming the quasi-normality and quasi-linearity of the studied function, this method provides approximate results. The results obtained following the methodology described in the GUM are then compared to the direct computation of the wall heat flux with altered temperatures. The study shows a dependence of the high heat flux estimation to some temperature variations, highlighting the necessity of accurate measurements. This is particularly salient in the end region of the solar receiver, i.e. when the bulk and the wall temperature are close. The GUM produces very satisfying estimations in the symmetric conditions and quite satisfying estimations in the asymmetric conditions. This study shows that the accuracy of measurement devices should be adapted according to their location in the solar receiver. Highlights: A heat transfer correlation is used to determine wall heat flux sensitivity. Uncertainty propagation in symmetric and asymmetric heating are compared. The general uncertainty management procedure provides reliable results. The bulk temperature and the cold wall temperature require accurate measurements. The uncertainty propagation is very dependent on the location in the solar receiver.